If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12y + -3 = 3y + 15 Reorder the terms: -3 + 12y = 3y + 15 Reorder the terms: -3 + 12y = 15 + 3y Solving -3 + 12y = 15 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -3 + 12y + -3y = 15 + 3y + -3y Combine like terms: 12y + -3y = 9y -3 + 9y = 15 + 3y + -3y Combine like terms: 3y + -3y = 0 -3 + 9y = 15 + 0 -3 + 9y = 15 Add '3' to each side of the equation. -3 + 3 + 9y = 15 + 3 Combine like terms: -3 + 3 = 0 0 + 9y = 15 + 3 9y = 15 + 3 Combine like terms: 15 + 3 = 18 9y = 18 Divide each side by '9'. y = 2 Simplifying y = 2
| -35=5d/11 | | 1x+10x-70+2x+3=180 | | (3+x)(x-12)=0 | | 7x+11-5x-2=2x-12 | | 4x+-7=x+8 | | 5y+2y^2=12 | | 2(1)/16 | | 6r-5r=2 | | 6x+6(x+2)=-28-8x | | solvef(x)=x^2-(4+4i)x+(1+8i) | | 4s=6g-23 | | 11=35-3d | | 2x/16 | | 11=3539 | | 5n+8=2n+13 | | 3s+7s=10 | | -8(y+9)=-48 | | 52=4u+8 | | 0.06x+0.09(15-x)=0.07*15 | | -2x=-4x-6 | | 5a+-10=10(a+3) | | (3-x)/20=2/5 | | 1/3(2x-3)=(2-4x) | | 3x^2y+2y=12 | | 7x-15=6x+8 | | 7=2b-3 | | 4x+11=41 | | 0.06x+0.09(15-x)=0.07 | | 3x-4=9-2x | | 2x=-4x-6 | | 6(2-7r)=-27 | | 15-3s=3 |